KARAKTERISTIK PETANI DAN KONTRIBUSI EKONOMI HUTAN KEMASYARAKATAN TERHADAP PENDAPATAN PETANI DI KPH TANAH LAUT - Prasetyo, Agung; Helmi, Muhammad; Rinakanti, Rinakanti (Universitas Lambung Mangkurat, 2024)
The social forestry program will undoubtedly have an impact on society, and each HKm in Indonesia provides varying contributions, just like in the KPH Tanah Laut. This research aims to identify the Characteristics of Forest Farmer Groups (KTH) in the Tanah Laut Forest Management Unit (KPH) and to analyze the contribution of Community Forests to forest farmers' income in the Tanah Laut KPH. The determination of respondent samples was intentionally done with the criteria being active members of KTH. The total number of respondents in this research was 56 respondents, calculated using the Slovin formula with a margin of error of 10%. The results of this research indicate that the Farmers' characteristics in KTH Kariya Jaya, KTH Harapan Baru, KTH Ingin Maju, and KTH Suka Maju consist of 85% male and 15% female. The average age of KTH members is above 51 years old. On average, they have an educational level of elementary school (SD) with 49.6%. The average number of dependents is 2 people. On average, KTH members manage land with an area of 0.5 hectares. The average occupation of KTH members is as private employees. The economic contribution of HKm in KTH Kariya Jaya accounts for 38%. The economic contribution of HKm in KTH Harapan Baru accounts for 55.2%. The economic contribution of HKm in KTH Ingin Maju accounts for 42.3%. The economic contribution of HKm in KTH Suka Maju is 46.9%.Program Perhutanan sosial sejatinya pasti akan memberikan dampak kepada masyarakat, setiap HKm di Indonesia memberikan kontribusi yang berbeda-beda sama halnya di KPH Tanah Laut. Penelitian ini bertujuan untuk Mengidentifikasi Karakteristik Kelompok Tani Hutan (KTH) di Kesatuan Pengelolaan Hutan (KPH) Tanah Laut, dan Menganalisis kontribusi Hutan Kemasyarakatan terhadap pendapatan petani hutan di KPH Tanah Laut. Penentuan sampel responden dilakukan secara sengaja dengan ketentuan sebagai anggota KTH yang aktif. Jumlah responden pada penelitian ini sebanyak 56 responden yang dihitung menggunakan rumus slovin dengan galad 10%. Hasil dari penelitian ini Karakteristik petani di KTH Kariya Jaya, KTH Harapan Baru, KTH Ingin Maju dan KTH Suka Maju memiliki Rasio Jenis Kelamin 85% laki-laki dan 15% berjenis kelamin perempuan. Umur rata-rata anggota KTH 51 tahun keatas. Rata-rata tingkat pendidikan SD 49,6%. Rata-rata memiliki tanggungan keluarga 2 orang. Rata-rata anggota KTH mengelola lahan seluas 0,5 ha. Pekerjaan anggota KTH rata-rata sebagai karyawan swasta. Kontribusi ekonomi HKm di KTH Kariya jaya sebesar 38%. Kontribusi ekonomi HKm di KTH Harapan Baru sebesar 55,2%. Kontribusi ekonomi HKm di KTH Ingin Maju sebesar 42,3%. Kontribusi ekonomi HKm di KTH Suka Maju adalah sebesar 46,9%.